Pretreatment alternatives for wastewater from oil tank farm and related oil product manufacturing - Ricarte, Hilario P., Jr.; Samorn Muttamara; Nguyen, Cong Thanh; Watanabe, Yoshimasa; Government of Japan (Bangkok : Asian Institute of Technology, 1981)
Shell CNS 'oil installation was utilized as a case study for its oily waste problem. Investigations were carried out on the existing treatment system believed to be ineffective. Sources and characteristics of waste~ water from oil tank farm and related oil product manufacturing were evalu- ated. Treatability studies of discharges with very high oil concentrations (mainly free oil and tempOrary emulsions) ranging from 70 to 2,240 mg/l were conducted using two types of 6il separators, namely, oil interceptor and compact plate separator (CPS). Performance of the oil interceptor~ a very simple form of gravity separator ·for oil-water mixtures,revealed a removal efficiency as high as 90% with effluent concentration of less than 15 mg/l oil and grease for a properly designed and maintained unit. Pilot-plant o~eration of the compact plate separator at the optimum flow rate of 2.5 m /h demonstrated an oil removal efficiency of more than 90% even without external heating. -However, better effluents were observed when it was coupled with an oil interceptor.serving as auxiliary unit. Both treatment systems are inexpensive from the point of view of a wealthy industry.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Sewage -- Purification -- Rotating disc process